Application of inorganic and liquid organic bio-fertilizers affects the vegetative growth and rhizobacteria populations of eight banana cultivars - Tri Handayani; Tirta Kumala Dewi; Diyah Martanti; Yuyu Suryasari Poerba; Sarjiya Antonius; Witjaksono WITJAKSONO (Society for Indonesian Biodiversity, 2021)
Abstract. Handayani T, Dewi TK, Martanti D, Poerba YS, Antonius S, Witjaksono. 2021. Application of inorganic and liquid organic bio-fertilizers affect the vegetative growth and rhizobacteria populations of eight banana cultivars. Biodiversitas 22: 1261-1271. Banana (Musa spp.) is generally cultivated subsistent as backyard crop or intensively in plantation with application of large amounts of inorganic fertilizers to improve yields. An application of bio-fertilizer may reduce the use of inorganic fertilizer and therefore may ensure sustainable production including banana production. This research evaluated the application of liquid organic bio-fertilizer (LOB) and inorganic fertilizers on vegetative growth and soil microbial population of banana plants. The LOB and inorganic fertilizer were tested in composition of (i) 100% inorganic fertilizer (NPK), (ii) 50% NPK + 100 % LOB, (iii) 100% LOB; on eight banana cultivars, i.e., Mas Kirana (AA), Cavendish (AAA), Barangan (AAA), Raja Bulu (AAB), Raja Lido (AAB), Raja Sereh (AAB), Tanduk (AAB), and Kepok (ABB). The results showed that for most of the cultivar tested, the vegetative growth rates were not significantly different between treatment of 100% NPK and LOB in combination with 50% NPK fertilizer. The LOB application improved soil microbial population, including PGPR with a specific function such as IAA producing, phosphate solubilizing, and protease enzyme activity. The application LOB alone was insufficient to support banana’s vegetative growth to the level incurred by even a moderate rate of inorganic fertilizer application.